(untitled) (Revista Contexto & Educação, 2025)
Written language at the University is often used to maintain power structures. Based on Freirean theory, this article discusses the potential of working with language through text within its context, considering micro and macro dimensions in teacher training.The objective of the article is to problematize these correlations of power in the relationship between university and school and the possible spaces for the construction of unstested feasibilities/inéditos viáveis in teacher training. The methodology is based on literature review and analysis of two activities carried out in the undergraduate course in Pedagogy in the second semester of 2023 and in the first semester of 2024. Based on the results, we found that students have been daring in their writing, reflecting a dialogue with the theory, based on pedagogically planned activities in disciplines, which invited undergraduates to articulate practice-theory, through written language.